Monte Carlo simulation in statistical physics an introduction - Binder, K. (Kurt) (Springer series in solid-state sciences, 1997)
This title deals with the computer simulation of thermodynamic properties of many-body condensed-matter systems that use random numbers generated by a computer in physics and chemistry. It describes the theoretical background of several variants of these Monte Carlo methods and gives a systematic course by which newcomers can learn to perform such simulations and to analyze their results. This third edition has been updated and a new chapter on some important recent developments of the Monte Carlo methodology was added.